Time-dependent effects of lead on rat reproductive functions - Kempinas, W. G. [UNESP]; Favaretto, A. L. V.; Melo, V. R.; Carvalho, T. L. L.; Petenusci, S. O.; Oliveira, R. M. (Wiley-Blackwell, 1994)
The effects of exposure to lead on endocrine function and the reproductive parameters were studied in pubertal rats treated with 1.0 g l(-1) lead acetate in drinking water for 20 days (subacute group) or 9 months (chronic group) in addition to i.v. injections of lead acetate (0.1 mg 100 g(-1) body wt.) every 10 (subacute group) or 15 days (chronic group). Although basal levels of testosterone were higher both in plasma and in testes of acutely intoxicated animals, the circulating levels of luteinizing hormone (LH) were not affected in either group, nor was the LH-releasing hormone content of the median eminence. The density of [I-125]LH/human chorionic gonadotrophin (hCG) binding sites in testicular homogenates was reduced by saturnism in both groups, concomitant with a significantly increased apparent affinity constant of the hormone-receptor complex. These data can be viewed as the result of a mixture of specific lead toxicity (e.g. at the enzyme level) with other more general actions (e.g. at the level of the hypothalamus-pituitary-testicular axis).
Keywords: LEAD EXPOSURE; TESTIS; TESTOSTERONE; HYPOTHALAMUS-PITUITARY-TESTICULAR AXIS; SEMINAL VESICLE; RAT